Reforming Representation: The Diffusion of Gender Quotas Worldwide - Mona Lena Krook (My University, 2016)
In recent years, more than a hundred countries have adopted quotas for the selection of female candidates to political office. Examining individual cases of quota reform, scholars offer four basic causal stories to explain quota adoption: Women mobilize for quotas to increase women’s representation, political elites recognize strategic advantages for supporting quotas, quotas are consistent with existing or emerging notions of equality and representation, and quotas are supported by international norms and spread through transnational sharing. Although most research focuses on the first three accounts, I arguer that the fourth offers the greatest potential for understanding the rapid diffusion of gender quota policies, as it explicitly addresses the potential connections among quota campaigns. In a theory-building exercise, I combine empirical work on gender quotas with insights from the international norms literature to identify four distinct international and transnational influences on national quota debates: international imposition, transnational emulation, international tipping, and international blockage. These patterns reveal that domestic debates often have international and transnational dimensions, at the same time that they intersect in distinct ways with international and transnational trends. As work on gender quotas continues to grow, therefore, I call on scholars to move away from simple accounts of diffusion to recognition of the multiple processes shaping the spread of candidate gender quotas worldwide.